Educação ambiental em Paraúna, Goiás: capacitação de professores para gestão de resíduos sólidos urbanos - Almeida, Lenimar Xavier de (2025)
The theme of urban solid waste (USW) management in the schools of Paraúna, Goiás State was presented as a concrete opportunity for a critical and emancipatory educational practice. This study, entitled “Environmental Education in Paraúna, Goiás State: teacher training for urban solid waste management,” focused on the teacher as a historical subject and agent of social transformation, capable of promoting change in both school and community contexts through environmental education. The research sought to answer the following question: how could teacher training contribute to strengthening Environmental Education in Paraúna within the context of urban solid waste management? The main objective was to design, implement, and evaluate a training course for Elementary School teachers, based on Freirean principles, aiming to strengthen teaching practice through critical, reflective, and contextualized education. The qualitative study was grounded in active listening and dialogue, creating formative spaces where teachers problematized reality, organized knowledge, and applied it in educational practices related to waste management. Activities such as workshops, discussion circles, and interdisciplinary projects articulated theory, pedagogical practice, and social commitment. The results showed that teacher training inspired by Freire’s pedagogy and anchored in local realities fostered more conscious and sustainable pedagogical practices, strengthening the sense of belonging and socio-environmental responsibility within the schools of the municipality. This dissertation is accompanied by the educational product available on the Educapes Platform at the following address: http://educapes.capes.gov.br/handle/capes/1174517.